2020
DOI: 10.1017/rdc.2020.79
|View full text |Cite
|
Sign up to set email alerts
|

When Did the Incas Build Machu Picchu and Its Satellite Sites? New Approches Based on Radiocarbon Dating

Abstract: According to the classical chronology of the Inca State, the ascension to power of Pachacuti Inca took place around AD 1438 and the construction of Machu Picchu began by AD 1450–1460. However, the improvement in the accuracy of radiocarbon (14C) dating resulting from the application of Bayesian analysis has changed our view of the historical chronology. This new research raises questions about our understanding of the cultural development of the Machu Picchu area, in the light of the new proposed chronological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…We believe that the differences between our results (Figure 3) and the earlier radiometric study are due to the limitations of the pre-treatment and other techniques utilised in the UCLA laboratory in 1988. In contrast, three AMS analyses made on carbonised wood from the architectural core of Machu Picchu published by Ziółkowski et al (2020) are consistent with the 26 analyses from the burial caves reported here (Table S3).…”
Section: Results and Chronological Implications For Machu Picchusupporting
confidence: 84%
See 2 more Smart Citations
“…We believe that the differences between our results (Figure 3) and the earlier radiometric study are due to the limitations of the pre-treatment and other techniques utilised in the UCLA laboratory in 1988. In contrast, three AMS analyses made on carbonised wood from the architectural core of Machu Picchu published by Ziółkowski et al (2020) are consistent with the 26 analyses from the burial caves reported here (Table S3).…”
Section: Results and Chronological Implications For Machu Picchusupporting
confidence: 84%
“…Although this produces slightly wider date ranges than either IntCal or SHCal, it is considered to yield "more accurate estimates of the dated samples and therefore, more robust comparisons to historic dates" (Marsh et al 2018: 933). A recent article presenting three radiocarbon measurements from Machu Picchu also employs a mixed calibration (Ziółkowski et al 2020). For these reasons, the dates presented here are also calibrated using this method (for comparisons of the different curves, see Table S5 and Figures S3-6).…”
Section: Challenges Of Radiocarbon-dating the Inca Empirementioning
confidence: 99%
See 1 more Smart Citation
“…The first stage is probably related to the phase just after the Incan conquest when the site was founded, whereas the second corresponds to the modifications or, in this case, the significant expansion of the site (Bastante et al, 2020; Masini et al, 2018). Interestingly, the first construction phase was also captured through laboratory analyses of coal elements found in the earliest structures, which indicates that the first construction phase took place at the very beginning of the 15th century (Ziółkowski et al, 2021). The second construction phase first involved the erection of canchas around the patio opposite the altar ( huaca ) and was associated with a significant expansion of the water system at the site.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the period of the dynamic development of the Inca State, as postulated by the historical chronology, was brief. However, recent dating studies based on the radiocarbon method have revealed several discrepancies in the historical chronology, suggesting that the expansion of the Inca State occurred over a longer time frame than has heretofore been understood (Ogbourn 2012;Marsh et al 2017;Ziółkowski et al 2020;Burger et al 2021). However, radiocarbon-based chronologies have presented discrepancies resulting from prior, different calibration curves.…”
Section: Introductionmentioning
confidence: 99%